2022
DOI: 10.3390/d14080668
|View full text |Cite
|
Sign up to set email alerts
|

Pore Water Chemical Variability and Its Effect on Phenological Production in Three Mangrove Species under Drought Conditions in Southeastern Mexico

Abstract: Mangrove forests have proven to be resilient to most environmental change, surviving catastrophic climate events over time. Our study aimed to evaluate the chemical variability of pore water and its effect on phenological production in three mangrove species (Rhizophora mangle, Avicennia germinans, and Laguncularia racemosa) along the coast of the state of Campeche during a year of severe drought (2009) and a year of average precipitation (2010). Pore water salinity and redox potential were measured monthly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…In addition, the dominance of A. germinans and presence of R. mangle and L. racemosa create suitable conditions for carbon sequestration [28][29][30]. The soil carbon sequestration at a depth of 30 cm in the mangroves in this study was similar to that reported at different sites in the state of Campeche by authors such as [1,31,32] (Table 1). This could have been due to environmental conditions, such as hydroperiod behavior, soil dynamics, and mangrove species productivity [33][34][35].…”
Section: Organic Carbon Sequestrationsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, the dominance of A. germinans and presence of R. mangle and L. racemosa create suitable conditions for carbon sequestration [28][29][30]. The soil carbon sequestration at a depth of 30 cm in the mangroves in this study was similar to that reported at different sites in the state of Campeche by authors such as [1,31,32] (Table 1). This could have been due to environmental conditions, such as hydroperiod behavior, soil dynamics, and mangrove species productivity [33][34][35].…”
Section: Organic Carbon Sequestrationsupporting
confidence: 86%
“…Mangroves form a coastal ecosystem that exhibits high productivity; they provide a variety of ecosystem services, such as carbon sequestration [1]. Therefore, they are considered to play an important role in mitigating the global warming caused by greenhouse gases (GHGs) owing to their ability to store carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Quadrats of 10 m × 10 m were laid randomly in the study site as per the standard ecological estimation method, to minimize biases in sampling. A similar method was also used by similar studies on mangrove biodiversity assessment across the globe [1,[25][26][27]. However, the dominant species has been the mangrove grass-P. coarctata (Relative density-78-88) and a frequency of 100 as observed between 2012-2016.…”
Section: Changes In Mangrove Community Ecologymentioning
confidence: 99%
“…In 1972 to 2004, prolonged drought due to less rainfall increased the vulnerability of mangroves in response to changing climate conditions in Australia [6]. Recent researches revealed that drought stress restrained mangrove growth and development [7]. As a result, protecting and restoring mangrove forests under extreme climatic conditions remains a major challenge [8].…”
Section: Introductionmentioning
confidence: 99%
“…K. obovata, the most cold-tolerant mangrove in China, faces imminent threats from extreme climate events, notably cold and drought stresses [7]. For instance, drought stress results in suppressed water absorption, closed stomata, and hindered CO 2 exchange in K. abovata [9,10].…”
Section: Introductionmentioning
confidence: 99%